Citrobacter diversus-derived keratinases and their potential application as detergent-compatible cloth-cleaning agents - Duffeck, Carlos Eduardo [UNESP]; Menezes, Cintia Lionela Ambrosio de [UNESP]; Boscolo, Mauricio [UNESP]; Silva, Roberto da [UNESP]; Gomes, Eleni [UNESP]; Silva, Ronivaldo Rodrigues da [UNESP] (Springer, 2020)
Currently, poultry farming is one of the sectors that have a significant impact on the global economy. In recent years, there has been an increase in the production of broilers, inflicting this segment of the industry to generate tons of keratin due to huge disposal of chicken feathers. This points to the need to degrade these chicken feathers, as they have emerged as a major threat to the environment. Thus, in this study we aimed to identify keratinases that are produced by the bacterium Citrobacter diversus and further investigate the biochemical characteristics of these keratin-degrading enzymes. In a submerged medium, the bacterium was capable of degrading chicken feathers almost completely after 36 h of fermentation. We found a maximum caseinolytic activity at pH 9-10.5 and 50-55 degrees C, and keratinolytic activity at pH 8.5-9.5 and 50 degrees C. Thus, given its stability at higher temperatures, upon incubation of this enzyme extract for 1 h at 50 degrees C, it showed approximately 50% of the keratinolytic and 100% of the caseinolytic activity. Further, under pH stability for 48 h at 4 degrees C, the enzyme extract maintained greater residual activity in the pH range 6-8. Caseinolytic activity was inhibited by EDTA and PMSF, whereas the keratinolytic activity was inhibited only by EDTA. Additionally, due to its alkaline activity and detergent compatibility, this enzyme extract could improve washing performance when added to a commercial detergent formulation. Using application tests, we could demonstrate a potential use of this bacterial enzyme extract as an additive in detergents to remove egg stains from cloth.
Keywords: Bacteria; Keratin; Enzyme; Keratinase; Sustainability; Detergent